IMPLEMENTATION OF PROTECTION AND EMPOWERMENT POLICIES MSME IN EAST JAVA BPR BANK - Albert Tito Setiawan; Arif Darmawan; Joko Widodo (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
PP Number 7 of 2021 concerning Ease of Protection and Empowerment of Cooperatives and MSMEs is a form of government policy in maintaining the existence of SMEs, especially in the midst of the Covid 19 pandemic crisis and when the Covid 19 endemic and as a form of government focus on developing SMEs in Indonesia.To maintain its business products, an SMEs need sufficient and adequate investment capital, especially to be used to deal with crises during the Covid 19 pandemic or when the Covid 19 endemic, therefore an SMEs need capital loans at a bank that specifically deals with SMEs, namely East Java BPR Bank. East Java BPR Bank is a bank that focuses on SMEs under the auspices of the East Java BUMD so that it differentiates it from other banks.The results of the study indicate that BPR Banks have implemented well the implementation of policies that have been made by the government PP No. 7 of 2021, especially on the Empowerment and Protection of SMEs through various types of capital loans with low interest rates of around 2-4% and capital borrowers can also maintain and develop its business products through the Fostered SMEs program held by East Java BPR Bank